Analysis of Tectonic Control Using Order and Bifurcation Ratio - Madani, Ghoffar Cahya; Sophian, Raden Irvan; Khoirullah, Nur (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
Quantitative geomorphological can be analyzed using watersheds morphometric aspect. Morphometry can be interpreted as a quantitative aspect of watersheds or parameters of watershed characteristics that can be measured and calculated. This research was shown to determine the tectonic control of the research area with the approach of the morphometric aspect of watershed. Aspect of watershed morphometry used in this research consist of river order and bifurcation ratio (Rb), drainage density (Dd), asymmetry factor (Af), mountain front sinuosity (Smf) and watershed shape index (Bs). The method used in this research is the studio method by processing Digital Elevation Model data using Arcmap software. Based on the results obtained, there are 4 sub-watersheds in the research area that have different calculation values. Sub-Watershed 1 has an Af value is (66,025), Smf value is (1.43 – 4.56), and Bs value is (1,002). Sub-Watershed 2 has an Af value is (51,398), Smf value is (1.38 – 3), and Bs value is (0.907). Sub-Watershed 3 has an Af value is (49,536), Smf value is (1.17 – 2.91), and Bs value is (0.933). Sub-Watershed 4 has an Af value is (60,407), Smf value is (1.8 – 3), and Bs value is (1,486). Based on all the calculation results, the relative tectonic activity index (IATR) value is 3 which belongs to class 4 which indicates low tectonic activity in the research area. This is also supported by the calculation of the bifurcation ratio where only a small part of the river segment is affected tectonics, meaning most of the others are not active tectonically.